Light sedation technique under BIS monitoring in extraction of mandibular impacted teeth: Application in 20 patients with dental anxiety - YU Tao; XIN Zhijun; SHANG Jiang; SUN Jing; QU Weidong (Kouqiang hemian waike zazhi)
[Objective:] To explore the application effect of light sedation technique in impacted tooth extraction in patients with anxiety. [Methods:] Intravenous infusion of propofol was administered to 20 patients with mandibular impacted teeth anxiety, and the impacted teeth were removed when the bispectral index (BIS) reached 80-85. The patients' heart rate (HR), mean arterial pressure (MAP), respiratory rate and blood oxygen saturation were monitored during operation, and the patients were instructed to record the visual analogue scale (VAS) after operation, and were asked about anterograde amnesia. SPSS 20.0 software package was used for data statistics, paired t test was used to compare the differences between intraoperative physiological indexes and the time of admission, and descriptive analysis was used to analyze the intraoperative pain of the patients. [Results:] All patients successfully completed the operation, and there were no obvious adverse reactions during the operation.There were no abnormalities in HR, MAP, respiratory rate and blood oxygen saturation. The postoperative VAS scores of the patients were 1-3, and the patients' anterograde amnesia of the start of surgery, mucosal incision and dental drill sound were recorded, which means that the anxiety was relieved. [Conclusion:] For the removal of mandibular impacted teeth in patients with dental anxiety, propofol intravenous light sedation technology (BIS=80-85) can achieve satisfactory results, reduce patients' anxiety and improve comfort.